2022
DOI: 10.1039/d1mo00495f
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of pseudoexfoliation aqueous humor lipidome

Abstract: Pseudoexfoliation syndrome (PEX) is a systemic disorder that manifests as fluffy, proteinaceous fibrillar material throughout the body. In the eye such deposits result in glaucoma (PEXG), due to impeding aqueous...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…These results revealed the importance of lipid metabolism equilibrium between blood endothelial cells and surrounding cells, for example corneal epithelium or keratocyte. Normal aqueous humor has been shown to contain more than 400 lipid species (Jahn et al, 1983;Collao et al, 2022;Liu et al, 2022), and the corneal endothelial cells serves as a dynamic barrier that separates aqueous humor from corneal stroma (Hasan and Fischer, 2021). It has been widely reported that increased intake of ω-3 long-chain polyunsaturated fatty acids (LCPUFA) diets reduce choroidal neovascularization in mice (Gong et al, 2016a;Gong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These results revealed the importance of lipid metabolism equilibrium between blood endothelial cells and surrounding cells, for example corneal epithelium or keratocyte. Normal aqueous humor has been shown to contain more than 400 lipid species (Jahn et al, 1983;Collao et al, 2022;Liu et al, 2022), and the corneal endothelial cells serves as a dynamic barrier that separates aqueous humor from corneal stroma (Hasan and Fischer, 2021). It has been widely reported that increased intake of ω-3 long-chain polyunsaturated fatty acids (LCPUFA) diets reduce choroidal neovascularization in mice (Gong et al, 2016a;Gong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Apolipoproteins are a group of key proteins participating in lipid metabolism and transport in the body. Apolipoproteins have been found to be part of the PEXM, especially in the pupillary area of the anterior lens capsule (Collao et al, 2022; Morris et al, 2021; Ronci et al, 2013). The APOE E2 allele was significantly linked to PEX development (Yilmaz et al, 2005).…”
Section: Pseudoexfoliative Glaucomamentioning
confidence: 99%